Spatial and temporal changes in assemblage structure of zooplankton and pelagic fish in the eastern Bering Sea across varying climate conditions - Lisa B. Eisner; Elizabeth C. Siddon; Wesley W. Strasburger (Известия ТИНРО)
Zooplankton and pelagic fish samples collected on the eastern Bering Sea shelf in late summer 2003-2010 were used to evaluate spatial and temporal changes in the plankton and nekton community structure. The zooplankton were sampled by vertical towing of a Juday net (168 μm mesh) and oblique towing of a Bongo net (505 μm mesh), and pelagic fish were caught by midwater rope trawl. The communities were compared across climate regimes (in relatively warm and cold years), by latitude (in the northern and southern parts of the shelf), and by water depth (in the inner, middle, and outer domains of the shelf). Zooplankton were dominated by the small copepod Oithona spp. in warm years but relatively larger copepods Pseudocalanus spp. and Acartia spp. in cold years. Notably, the large copepod Calanus spp., an important energy-rich prey for fish, were more abundant in cold years than warm years. Age-0 walleye pollock Gadus chalcogrammus were more abundant in warm years, while capelin Mallotus villosus were abundant within cold-year communities over the northern shelf. Latitudinal variations in communities were more prominent in the cold years, particularly in 2007 and 2010. Cross-shelf variations were evident, particularly for large zooplankton and fish, with communities corresponding to specific oceanographic domains. Outer shelf communities varied less than inner and middle shelf communities between warm and cold periods, suggesting that this region may be less impacted by climate variability. An understanding of the overlap of zooplankton (prey) and fish communities within specific shelf regions or climate regimes may provide information for ecosystem-based approaches to fisheries management.